Evaluasi Program Kampus Mengajar dengan Model Context, Input, Process, Product (CIPP) - Annisa Paquita RF; Sunarni Sunarni; Ahmad Yusuf Sobri (Universitas Negeri Malang, 2023)
Abstract: This study aims to evaluate the campus teaching program by using the context, input, process, product (CIPP) evaluation model at the State University of Malang. This research is an evaluative research with a quantitative approach. Data collection was done through a questionnaire created using Google Form and distributed via Whatsapp and Twitter. The data analysis technique used descriptive analysis. The research subjects included Malang State University students who attended the teaching campus 4, totaling 201. The results showed: (1) Evaluation of the teaching campus program with the CIPP model as a whole is in very good criteria, which means that teaching campus activities have been carried out in accordance with campus regulations / guidebooks; (2) Evaluation in the context aspect of the teaching campus program, is in very good criteria, which means that students are able to understand the purpose of implementation, vision and mission and the benefits of the program; (3) Evaluation in the input aspect of the teaching campus program is in the very good category, which means that student needs have been met properly; (4) Evaluation of the process aspect of the teaching campus program is in the excellent criteria, which means that students are able to carry out the teaching campus program at school and are active in all its activities; (5) Evaluation of the product aspect of the teaching campus program is in the excellent criteria, which means that students gain increased skills through this activity; (6) No differences were found in the CIPP evaluation of the teaching campus program based on class, faculty, and gender.Keywords: Program Evaluation; CIPP Evaluation Model; Teaching Campus Abstrak: Penelitian ini bertujuan mengevaluasi program kampus mengajar dengan menggunakan model evaluasi context, input, process, product (CIPP) di Universitas Negeri Malang. Penelitian ini merupakan penelitian evaluatif dengan pendekatan kuantitatif. Pengumpulan data dilakukan melalui angket yang dibuat menggunakan Google Form dan disebarkan melalui Whatsapp dan Twitter. Teknik analisis data menggunakan analisis deskriptif. Subjek penelitian meliputi mahasiswa Universitas Negeri Malang yang mengikuti kampus mengajar 4 yang berjumlah 201. Hasil penelitian menunjukkan: (1) Evaluasi program kampus mengajar dengan model CIPP secara keseluruhan berada pada kriteria sangat baik, yang berarti kegiatan kampus mengajar sudah dilaksanakan sesuai dengan ketentuan/buku panduan kampus; (2) Evaluasi pada aspek context program kampus mengajar, berada pada kriteria sangat baik yang berarti mahasiswa mampu memahami tujuan pelaksanaan, visi misi dan manfaat program; (3) Evaluasi pada aspek input program kampus mengajar berada di kategori sangat baik, yang berarti kebutuhan mahasiswa sudah terpenuhi dengan baik; (4) Evaluasi pada aspek process program kampus mengajar berada pada kriteria sangat baik, yang berarti mahasiswa mampu melaksanakan program kampus mengajar di sekolah dan aktif dalam semua kegiatannya; (5) Evaluasi aspek product program kampus mengajar berada pada kriteria sangat baik, yang berarti mahasiswa memperoleh peningkatan keterampilan melalui kegiatan ini; (6) Tidak ditemukan adanya perbedaan pada evaluasi CIPP program kampus mengajar berdasarkan angkatan, fakultas, dan jenis kelamin.Kata kunci: Evaluasi Program; Model Evaluasi CIPP; Kampus Mengajar